Places & Spaces: A Critical Analysis of Cancer Disparities and Access to Cancer Care Among First Nations Peoples in Canada - Tara Horrill; Josee Lavoie; Donna Martin; Annette Schultz (York University Libraries, 2020)
Despite advancements in research and medicine, health inequities and disparities among First Nations peoples (FN) in Canada are well documented and continue to grow. Once virtually unheard of, cancer now is a leading cause of death among FN. Many factors contribute to cancer disparities, but FN face unique challenges in accessing healthcare. In this critical review and analysis, we explore potential links between cancer disparities and poor access to cancer care among FN. Research suggests FN experience difficulty accessing cancer services in several 'places' of care, including screening, diagnosis, treatment, survivorship and palliative care. Furthermore, there are notable 'spaces' or gaps both within and between these 'places' of care likely contributing to cancer disparities among First Nations. Gaps in care result from jurisdictional ambiguities, geographical location, unsafe social spaces, and marginalization of FN ways of knowing, and can be linked to colonial and neocolonial policies and ideologies. By drawing attention to these broader structural influences on health, we aim to challenge discourses that attribute growing cancer disparities among FN in Canada solely to increases in 'risk factors'.